THE INFLUENCE OF LEARNING ACTIVITIES AND LEARNING MEDIA ON LEARNING OUTCOMES OF CLASS VIII HEALTH OF EDUCATION STUDENTS AT SMPN 1 KALIBARU - Dicky Retmawadi (Journal of Education Technology and Inovation, 2022)
Learning outcomes on the one hand are thanks to the actions of the teacher, as an achievement of learning objectives. Learning outcomes can be divided into teaching impacts and accompaniment impacts. Both of these impacts are very useful for teachers as well as students. The impact of teaching is a measurable outcome, such as the report card number, the number on the diploma, or the ability to jump after training. Learning factors can be influenced by activity factors that can affect the achievement of learning outcomes. Training factors so that students can understand the material that has been delivered, the atmosphere factor so that students can study calmly, the association factor that can provide a learning experience, the learning readiness factor in order to achieve maximum learning outcomes, the interest and effort factors must be in line so that students can learn optimally , physiological factors must be considered because physiological factors determine the success of students in learning, intelligence factors are very concerned about knowing how students think in making decisions. The sampling technique used was simple random sampling. For testing the first, second and third hypotheses using simple linear regression, while for the fourth hypothesis using multiple linear regression. Based on the data analysis and hypothesis testing that has been done, the conclusions in this study can be formulated as follows: There is an effect of learning activities and learning media together on the learning outcomes of Physical Education for Class VIII students of SMP N 1 Kalibaru Banyuwangi